2012
DOI: 10.1111/j.1349-7006.2012.02411.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tumor‐associated macrophages on invasive ductal carcinoma of the pancreas head

Abstract: Tumor-associated macrophages (TAMs) are candidate histological factors in invasive ductal carcinoma (IDC) of the pancreas. Tumorassociated macrophages can be affected by cancer-related inflammation and pancreatitis and interact with important invasive behavior in a recurrent manner in pancreatic IDC. These features may help elucidate the aggressiveness of pancreatic IDC. The aim of this study was to characterize TAMs in pancreatic IDC in comparison with chronic pancreatitis (CP) and to reveal TAM-related facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
109
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(115 citation statements)
references
References 43 publications
6
109
0
Order By: Relevance
“…BxPC-3 cells co-cultured with PBMCs displayed significantly higher invasive capabilities than BxPC-3 cells cultured alone, in accordance with the tumour-promoting role of TAMs (P<0.001; Fig. 7a-b Previous studies on pancreatic cancer-related inflammation have shown enhanced leukocyte infiltration in the tumour microenvironment and elevated systemic cytokine levels in patients with pancreatic cancer [26][27][28][29][30] . Macrophages, in particular with an alternatively activated M2-associated phenotype, were among the most common leukocyte subsets infiltrating the tumour area 29, 30 .…”
Section: Tumour-educated Macrophages and Hyperglycaemia Promote Invassupporting
confidence: 51%
See 1 more Smart Citation
“…BxPC-3 cells co-cultured with PBMCs displayed significantly higher invasive capabilities than BxPC-3 cells cultured alone, in accordance with the tumour-promoting role of TAMs (P<0.001; Fig. 7a-b Previous studies on pancreatic cancer-related inflammation have shown enhanced leukocyte infiltration in the tumour microenvironment and elevated systemic cytokine levels in patients with pancreatic cancer [26][27][28][29][30] . Macrophages, in particular with an alternatively activated M2-associated phenotype, were among the most common leukocyte subsets infiltrating the tumour area 29, 30 .…”
Section: Tumour-educated Macrophages and Hyperglycaemia Promote Invassupporting
confidence: 51%
“…7a-b Previous studies on pancreatic cancer-related inflammation have shown enhanced leukocyte infiltration in the tumour microenvironment and elevated systemic cytokine levels in patients with pancreatic cancer [26][27][28][29][30] . Macrophages, in particular with an alternatively activated M2-associated phenotype, were among the most common leukocyte subsets infiltrating the tumour area 29, 30 . This was further reflected in the systemic cytokine levels, where IL-6, IL-8 and IL-10 were elevated in pancreatic cancer patients [26][27][28] .…”
Section: Tumour-educated Macrophages and Hyperglycaemia Promote Invasmentioning
confidence: 99%
“…The studies showing that high infiltration by M2 macrophages in tumour tissue is associated with poor prognosis in pdac patients 11,12,17 were conducted in Japan. Being that no study had yet been conducted in China, we set out to determine any correlations of tam and M2 macrophage counts with prognosis in Chinese patients with pdac.…”
Section: Discussionmentioning
confidence: 99%
“…Counting of CD68 and CD163 immunoreactivity-positive membrane or cytoplasm and nonreactive nuclei was performed under light microscopy (Olympus CX-40: Olympus, Tokyo, Japan). Macrophages were counted separately in the peripheral and central areas of lesions as described in an earlier study 17 . The means of the counts from 3 random high-power fields (400× magnification) were used in the analyses.…”
Section: Immunohistochemistry For Cd68 and Cd163mentioning
confidence: 99%
“…M1-like TAMs, however, are sparse and confined to the less hypoxic regions of tumors (15). The presence of M2-like TAMs in tumors correlates with poor prognosis (16,17), whereas the presence of M1-like TAMs correlates with longer survival for patients (18).…”
Section: Introductionmentioning
confidence: 99%